PERSPEKTIF KELEMBAGAAN EKONOMI PETANI DALAM MENDUKUNGPERKEMBANGAN PEREKONOMIAN PERDESAAN / Role of Farmers’ Economic Institution in Supporting RuralEconomics Development - Cut Rabiatul Adawiyah; S. Rusdiana; Saptana Saptana (Jurnal Penelitian dan Pengembangan Pertanian, 2022)
Farmers’ economic institutions have a very important role in thedevelopment of agribusiness, both as a system and as a business.Increasing the competitiveness of agricultural products in the midstof global market competition can be realized through a strategyof transforming farmer institutions towards reliable farmereconomic institutions, agricultural businesses can be managedefficiently with professional human resources and support forconducive government policies, which are expected to produceagricultural and livestock products that are capable of producinghigh quality agricultural products. create added value and strongcompetitiveness, both in domestic and global markets. Developplans for the future so that the farmers’ economy can improve, aswell as look for leverage points that can encourage or triggerfarmers’ welfare. Increased absorption of labor in rural areasencourages other businesses related to agribusiness and theprovision of infrastructure to support economic progress in thecommunity. Institutional support for farmer groups that have beendeveloped is more oriented to agricultural businesses, to produceproducts and strengthen community economic networks based onlocal resources. The agricultural sector during the Covid-19pandemic can actually be used as a strategy for recovery and atthe same time provides the basis for the development of the realsector of economic progress. Strengthening the economy of farmerscan be pursued through support for strengthening farmerinstitutions, guidance, counseling, capital assistance, agriculturalfacilities and facilities, availability and access to input and outputmarkets, as well as policy support and facilitation of central andregional governments.Keywords: Agricultural institutions, perspective, rural, farmer’s economy AbstrakKelembagaan ekonomi petani mempunyai peranan yang sangatpenting dalam pengembangan agribisnis, baik sebagai sistemmaupun usaha. Peningkatan daya saing produk pertanian di tengahpersaingan pasar global dapat diwujudkan melalui strategitranformasi kelembagaan petani ke arah kelembagaan ekonomipetani yang andal, usaha pertanian dapat dikelola secara efisiendengan SDM profesional dan dukungan kebijakan pemerintah yangkondusif, diharapkan dapat menghasilkan produk pertanian danpeternakan yang mampu menciptakan nilai tambah dan daya saingyang kuat, baik di pasar domestik maupun global. Menyusun rencanauntuk ke depan agar perekonomian petani meningkat, sekaligusmencari titik ungkit yang dapat mendorong atau memicukesejahteraan petani. Peningkatan serapan tenaga kerja diperdesaan mendorong usaha-usaha lain yang berkaitan denganagribisnis dan penyediaan prasarana sebagai pendukung kemajuanperekonomian di masyarakat. Dukungan kelembagaan kelompokpetani yang dikembangkan lebih berorientasi pada usaha pertanian,untuk menghasilkan produk dan memperkuat jaringan ekonomikerakyatan berbasis sumber daya lokal. Sektor pertanian pada masapandemi Covid-19 sesungguhnya dapat dijadikan salah satustrategi untuk pemulihan dan sekaligus memberikan landasaanperkembangan sektor riil kemajuan perekonomian. Penguatanekonomi petani dapat diupayakan melalui dukungan penguatankelembagaan petani, bimbingan, penyuluhan, bantuan permodalan,sarana dan sarana pertanian, ketersediaan dan akses ke pasar inputdan output, serta dukungan kebijakan dan fasilitasi pemerintahpusat dan daerah.Kata Kunci: Kelembagaan pertanian, perspektif, perdesaan,ekonomi petani